Neonatal brain injury and systemic inflammation: modulation by activated protein C ex vivo. (16th February 2015) - Eliwan, H O; Watson, R W G; Aslam, S; Regan, I; Philbin, B; O'Hare, F M; O'Neill, A; Preston, R; Blanco, A; Grant, T; Nolan, B; Smith, O; et al.
Summary: Infection and inflammation can be antecedents of neonatal encephalopathy (NE) and increase the risk of neurological sequelae. Activated protein C (APC) has anti-coagulant and anti-inflammatory effects and provides neuroprotection in brain and spinal cord injury. We examined neutrophil and monocyte responses to lipopolysaccharide (LPS) in infants with NE compared with healthy adult and neonatal controls, and also studied the effect of APC. Whole blood was incubated with LPS and APC and Toll-like receptor (TLR)-4 (LPS recognition), CD11b expression (activation) and intracellular reactive oxygen intermediate (ROI; function) release from neutrophils and monocytes was examined by flow cytometry serially from days 1 to 7. We found a significant increase in neutrophil ROI in infants with NE on day 3 following LPS compared to neonatal controls and this augmented response was reduced significantly by APC. Neutrophil and monocyte CD11b expression was increased significantly on day 1 in infants with NE compared to neonatal controls. LPS-induced neutrophil TLR-4 expression was increased significantly in infants with NE on days 3 and 7 and was reduced by APC. LPS-induced monocyte TLR-4 was increased significantly in infants with NE on day 7. Neutrophil and monocyte activation and production of ROIs may mediate tissue damage in infants with NE. APC modified LPS responses in infants with NE. APC may reduce the inflammatory responses in NE and may ameliorate multi-organ dysfunction. Further study of the immunomodulatory effects of protein C may be warranted using mutant forms with decreased bleeding potential.